FACTORS CONTRIBUTING TO LOW USE OF TUBAL LIGATION AMONG WOMEN ATTENDING FAMILY PLANNING SERVICES AT RUHOKO HEALTH CENTRE IV, IBANDA DISTRICT. - Ayebazibwe , Anakiret; Tushaba , Ohurira (Student’s Journal of Health Research Africa, 2023)
Background. The purpose of this study was to identify the level of utilization of tubal ligation among women attending the MCH clinic at Ruhoko Health Centre IV Ibanda District and the factors that may influence the utilization of such contraceptive methods. Methodology: I carried out a cross-sectional study and I used a pretested questionnaire to collect data from 52 respondents. Collected data was entered into IBM SPSS 25.0 for data analysis chi-square test was done to determine factors associated with the use of ligation. Results were presented in tables and charts. Results: The study findings on socio-demographic factors found that the majority (75%) of respondents were aged >30 years, most (54%) of respondents reported that the distance to the health facility was too far for them and the prevalence of tubal ligation was low (32.7%). Factors associated with low use of tubal ligation were; the mother’s age ≥ 30 years and a current number of children ≥4. i.e. (X2=10.71; p=0.001) and (X2=97.47; P=<0.001) respectively. Conclusion: The prevalence of tubal ligation uses among women attending the MCH clinic at Ruhoko Health Centre IV was low (32.7%) as compared to short-acting contraceptive methods (67.3%). Significant factors associated with the use of tubal ligation were women’s age ≥ 30 years and parity ≥ 4. Recommendation: This study recommends that health workers in MCH and stakeholders should come up with ways to increase the utilization of tubal ligation methods of contraception among women < 30 years old and parity ≤ 3. Finally, more research should be done to ascertain the reason why the prevalence of tubal ligation is low.